2020
DOI: 10.3390/ijerph17072537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Indoors Artificial Lighting Conditions on Computer-Based Learning Performance

Abstract: Lighting condition is essential to human performance. With the widespread use of computer-based learning, the performance measurements become difficult, and the effects of artificial lighting conditions towards the new learning forms are not investigated extensively. The current study conducts a subject-within experiment with a 45-min-long online learning along with electroencephalogram (EEG)-based measurements, and a post-interview under five lighting setups respectively (300 lx, 3000 K; 300 lx, 4000 K; 300 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Studies of changes in brain waves in environmental and spatial stimuli have been conducted on a variety of topics, including studies of human emotions and relationships with architectural space [ 36 , 37 , 38 ], stress and anxiety [ 11 , 39 , 40 ], studies of positive and negative emotions [ 41 , 42 ], concentration and attention [ 43 , 44 ], and cognitive and emotional processing [ 9 , 14 , 45 ]. These studies have demonstrated that EEG is an appropriate tool for achieving research objectives.…”
Section: Application Of Vr-eeg In Architectural Researchmentioning
confidence: 99%
“…Studies of changes in brain waves in environmental and spatial stimuli have been conducted on a variety of topics, including studies of human emotions and relationships with architectural space [ 36 , 37 , 38 ], stress and anxiety [ 11 , 39 , 40 ], studies of positive and negative emotions [ 41 , 42 ], concentration and attention [ 43 , 44 ], and cognitive and emotional processing [ 9 , 14 , 45 ]. These studies have demonstrated that EEG is an appropriate tool for achieving research objectives.…”
Section: Application Of Vr-eeg In Architectural Researchmentioning
confidence: 99%
“…One study used EEG physiological signal monitoring techniques to gain new insights into how people perceive architectural environment features and design [25]. Olszewska et al [26] used EEG to examine how different levels of green cover visible from various floors affected 29 healthy residents.…”
Section: Landscape Design and Eegmentioning
confidence: 99%
“…Generally, when the lighting level is around 1000 lx, employees tend to perform better compared with working in a low light level of 200 lx. Lighting quality by itself is not a determinant of work performance, but lighting quality influences visual aspects which in turn influence work performance [ 10 ].…”
Section: Literature Reviewmentioning
confidence: 99%